2021
DOI: 10.1186/s12967-021-02798-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy may protect cancer patients from SARS-CoV-2 infection: a single-center retrospective analysis

Abstract: Coronavirus disease 2019 (COVID-19) global pandemic has created unique challenges to healthcare systems throughout the world. Ensuring subjects’ safety is mandatory especially in oncology, in consideration of cancer patients’ particular frailty. We examined the proportion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgM and/or IgG positive subjects in three different groups from Istituto Nazionale Tumori – IRCCS “Fondazione G. Pascale” in Naples (Campania region, Italy): cancer patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
(28 reference statements)
0
11
0
2
Order By: Relevance
“…Figure 1 shows the PRISMA flow chart for the study screening and selection process in this research. Twenty-three trials including 19 retrospective studies [21] , [23] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] and 4 prospective studies [22] , [42] , [43] , [44] , enrolling 117735 study subjects ultimately met our criteria ( Figure 1 ). Six studies were performed in USA [25] , [26] , [29] , [31] , [35] , [40] , five in Italy [27] , [28] , [38] , [39] , [42] , four in Spain [27] , [36] , [37] , [43] , three in United Kingdom [22] , [33] , [34] , two in China [23] , [30] , one in France [41] , one in India [32] and one in Australia [21] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the PRISMA flow chart for the study screening and selection process in this research. Twenty-three trials including 19 retrospective studies [21] , [23] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] and 4 prospective studies [22] , [42] , [43] , [44] , enrolling 117735 study subjects ultimately met our criteria ( Figure 1 ). Six studies were performed in USA [25] , [26] , [29] , [31] , [35] , [40] , five in Italy [27] , [28] , [38] , [39] , [42] , four in Spain [27] , [36] , [37] , [43] , three in United Kingdom [22] , [33] , [34] , two in China [23] , [30] , one in France [41] , one in India [32] and one in Australia [21] .…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of COVID-19 and clinical outcome of cancer patients with COVID-19 infection prior exposure to ICIs are controversial. The study conducted by Maria Antonietta Isgrò have showed that ICIs could protect cancer patients from COVID-19 infection [28] . However, another real-world study performed by Alexia Francesca Bertuzzi did not show a high risk for COVID-19 infection in cancer patients treated with ICIs [39] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 95 ] Evidence shows that programmed cell death protein 1 (anti-PD 1) or cytotoxic T-lymphocyte–associated antigen 4 (CTLA-4) immunotherapy may even protect cancer patients from COVID-19 infection. [ 96 97 ] The rate of immune checkpoint inhibitor-associated adverse has not been shown to be increased in COVID-19-infected patients. On the other hand, the mortality rate as a repercussion of COVID-19 infection in this cohort of cancer patients appears to be increased.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in sepsis or infection after pneumonia and inflammatory response syndrome was observed in COVID-19 patients administered with PD-1 inhibitors (146). ICIs would likely to be a protective factor against the onset of COVID-19 infection (159). Ruxolitinib a Janus-associated kinase (JAK) inhibitor has been reported to reduce cytokine-mediated inflammation, reducing severe events such as ARDS in COVID-19 infected patients, and many trials are currently active (146).…”
Section: Ethical Approvalmentioning
confidence: 99%